Effect of Anti Mullerian Hormone (AMH) on Hyperthyroidism with and without polycystic ovarian syndrome (PCOS) in female patients - M.A Al-Qaisi, Samah; M.J Al-Shammaa, Nawal (Iraqi Journal of Science, 2021)
Effect Anti-Mullerian Hormone (AMH) on thyroid levels in patients with andwithout polycystic ovarian syndrome PCOS was studied, The results showed anincrease in AMH ,T3 ,T4 with increase of age while TSH , BMI decreased withincrease of age comparing to control in hyperthyroidism with PCOS patients.Otherwise an increase in AMH, TSH, BMI, T3 and T4 with increase of Agecompared to healthy group in hyperthyroidism without PCOS. Effect of ovarianhormones (AMH) on inventory levels of thyroid and perturbations in terms ofincreases and its impact obesity as well as fertility in women was declared in thisresearch. Serum Anti-Müllerian Hormone (AMH) was assessed using enzyme linkedimmunosorbent kit [Elisa] while Thyroid stimulating hormone (TSH),Triiodothyronine (T3), Thyroxin (T4) were determined by VIDAS kitmethod(enzyme linked fluorescent assay).